(untitled) (Bangladesh Journal of Medical Science, 2022)
Objective:The study aimed to evaluate the clinical efficacy, early and long-term outcomes of a modified surgical treatment method of convergent concomitant strabismus in children. Materials and methods: Thestudy enrolled 159 children (88 girls (55.3%) and 71 boys (44.7%)) aged 4 to 8 years (mean age, 6.05 ± 0.82 years) suffering from convergent concomitant strabismus. Of a total number, 57 children underwenttraditionalsurgicalintervention(controlgroup), and102 children underwent surgical intervention with the proposed modified approach (main group). Results and Discussion: In the distant timeframe (1-3 years after surgery), 141 children were examined.Inthe remotepostoperativeperiod,thecorrect eyeposition was preserved in 46 children (49.5%) in the main group vs.5children (10.4%) in the control group (OR = 8.42, 95% CI [3.06- 23.14], p<0.05). A secondary deviation occurred in 3 main group children (3.2%) compared to 7 control group children (14.6%) (OR = 5.12, 95% CI [1.26-20.81], p<0.05). In the long-term period, 32 (34.4%) childrenin the main group and 30 (62.5%) in the control group required repeated surgery to eliminate secondary divergent strabismus and residual deviation angle (OR = 3.18, 95% CI [1.54-6.56],p<0.05). Conclusion. Thus, the proposed modified surgical treatment method of convergent concomitant strabismus in children is more effective than traditional methods. Bangladesh Journal of Medical Science Vol. 21 No. 03 July’22 Page: 570-576